Navigating life with HIV as an older adult on the Kenyan coast: perceived health challenges seen through the biopsychosocial model - Mwangala, PN; Wagner, RG; Newton, CR; Abubakar, A (Frontiers Media, 2023)
Objectives: This study explores the perceptions of adults living with HIV aged ≥50 years (recognized as older adults living with HIV—OALWH), primary caregivers and healthcare providers on the health challenges of ageing with HIV at Kilifi, a low literacy setting on the coast of Kenya.